2017
DOI: 10.3329/ajmbr.v3i2.33575
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary probiotics as antibiotic alternative on growth performance, organ development and meat quality in broiler chicken

Abstract: Abstract:The aim of the study was to evaluate the effect of dietary probiotics on broiler growth performance, organ development and meat quality in replacing oxytetracycline. Dietary treatments were control (basal diet without additives), antibiotic (basal diet with 0.05% oxytetracycline), basal diet with Bacillus subtilis and basal diet with Lactobacillus spp. A total of 192 birds were randomly allotted to four dietary treatments with four replicates having 12 birds each. Feed and water were supplied ad libit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…No differences (p > 0.05) were observed in drip, cooking and thaw losses on breast muscle between diets. Sarker et al (2017) showed that the use of probiotic as an alternative to antibiotics does not affect water losses during cooking in broilers. The rise in temperature during cooking causes a total destruction of the cell wall of muscle tissue, which in turn causes a release of very large amounts of liquids.…”
Section: Physicochemical Parametersmentioning
confidence: 99%
“…No differences (p > 0.05) were observed in drip, cooking and thaw losses on breast muscle between diets. Sarker et al (2017) showed that the use of probiotic as an alternative to antibiotics does not affect water losses during cooking in broilers. The rise in temperature during cooking causes a total destruction of the cell wall of muscle tissue, which in turn causes a release of very large amounts of liquids.…”
Section: Physicochemical Parametersmentioning
confidence: 99%
“…In cooking loss in broiler no difference was reported, regardless of probiotic feeding levels [165,168,169]. Also, the drip, cooking, and thaw losses on breast muscle were not observed by Benamirouche et al [157].…”
Section: Meat Qualitymentioning
confidence: 87%
“…Similar findings by Sulistiani 128 also reported enzymatic activities (amylase, and phytase) by LAB strains isolated from Borassus flabellifer palm wine. Reports have shown that LABs exhibiting enzymatic activities improved growth performance 129,130 and enhanced nutrient digestion, especially in newly hatched chicks 131,132 . The production of the beta-galactosidase enzyme in high amounts enhanced lactose digestion 133,134 , while the bile salt hydrolase (BSH) enzyme reduced serum cholesterol through increased synthesis of bile salts from serum cholesterol and decreased uptake from the gut 135 .…”
Section: Alcoholsmentioning
confidence: 99%